Morphology of immature stages of blow fly, Lucilia sinensis Aubertin (Diptera: Calliphoridae), a potential species of forensic importance - Sangob Sanit (2018)
© 2017 Elsevier B.V. Lucilia sinensis Aubertin (Diptera: Calliphoridae) is a blow fly species of potential forensic importance since adults are attracted to, and colonize, decomposing vertebrate remains. Blow fly larvae associated with human corpses can be useful evidence in forensic investigations; however, their use is dependent in most cases on proper species identification and availability of developmental data. For identification, morphological information on each life stage is traditionally used. We used scanning electron microscopy (SEM) to examine the ultrastructure of eggs, all instars, and puparia, of L. sinensis. The important characteristics used to differentiate L. sinensis from other species are provided. Distinctive features of the eggs are the slight widening median area extending almost the entire length. The last abdominal segment of the first instar bears elongated outer ventral tubercles along the rim of the last abdominal segment. These tubercles, as well as the well developed median and outer dorsal tubercles, are more prominent in the second and third instars. The surface integument of the tubercles is equipped with circular rows of microtrichia. Pairs of inner dorsal tubercle are absent. Each anterior spiracle is comprised of 9–12 papillae arrange in a single row in the second and third instars. As for the third instar, the dorsal spines between the first and second thoracic segments are delicate, narrow, small, and close together (as row or set). The peristigmatic tufts adjacent to the posterior spiracle of the third instar are moderately branches of short, fine hairs, but minute in puparia. In conclusion, the prominent outer ventral tubercle in all instars and puparia is a new diagnostic feature of L. sinensis and helpful in differentiating it from other Lucilia species that are forensically important. The description of immature L. sinensis in this study will be useful for forensic entomologists in countries where this species exists.